2010
DOI: 10.1007/bf03395739
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Relational Assessment Procedure As a Measure of Self-Esteem

Abstract: Two studies were conducted to pilot the Implicit Relational Assessment Procedure (IRAP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
9
0
5
Order By: Relevance
“…Evidence for discriminant validity may further be inferred from studies that have shown differential effects of an intervention on IRAP versus explicit measures of the same target (Cullen et al, 2009;Hooper et al, 2010;Scheel, Fischer, McMahon, Mena, & Wolf, 2011 Two further articles report significant correlations between IRAP and explicit indices of the same targets Timko, England, Herbert, & Forman, 2010). However, these studies examined many relationships (e.g., 100 correlations across two studies in Timko et al, 2010) without adjusting for multiple testing and findings could partially reflect an inflated Type I error-rate.…”
Section: Experimental Experimental Validity Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for discriminant validity may further be inferred from studies that have shown differential effects of an intervention on IRAP versus explicit measures of the same target (Cullen et al, 2009;Hooper et al, 2010;Scheel, Fischer, McMahon, Mena, & Wolf, 2011 Two further articles report significant correlations between IRAP and explicit indices of the same targets Timko, England, Herbert, & Forman, 2010). However, these studies examined many relationships (e.g., 100 correlations across two studies in Timko et al, 2010) without adjusting for multiple testing and findings could partially reflect an inflated Type I error-rate.…”
Section: Experimental Experimental Validity Ismentioning
confidence: 99%
“…Criterion validity refers to how strongly IRAP scores are related to other behaviours and psychological attributes. Two further articles report significant correlations between IRAP and explicit indices of the same targets Timko, England, Herbert, & Forman, 2010). However, these studies examined many relationships (e.g., 100 correlations across two studies in Timko et al, 2010) without adjusting for multiple testing and findings could partially reflect an inflated Type I error-rate.…”
Section: Experimental Experimental Validity Is Evident When Manipulamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we aimed at usefulness of a relatively new latency-based measure of ISE. The analysis concerning trial type scores showed that positivity bias, typical of ESE but also frequently observed in ISE assessed using various measures (Bosson et al, 2000;Greenwald & Farnham, 2000;Gregg & Sedikides, 2010;Timko, England, Herbert, & Forman, 2010), was present for three trial type scores (Self-Positive, Self-not Positive, Self-not Negative) but was not present in the case of self-negative scores (when the participants responded consistently with the rule assuming the possession of negative traits). In other words, responses of the participants, regardless of their level of narcissism, do not indicate a clear rejection of negative traits ascribed to the self.…”
Section: Discussionmentioning
confidence: 92%
“…The best way to gain self-confidence is to look deep inside of yourself and believe that you have the ability to overcome all obstacles and challenges that you are faced with, on a daily bases, because our self-esteem is one of the few things that we have control over. (Timko, 2010(Timko, : 2113 Self-confidence is something that cannot be taught. It is up to the individual to decide how much belief that they possess inside of themselves.…”
Section: Introductionmentioning
confidence: 99%